Novel cellular entities and their role in the etiopathogenesis of female idiopathic infertility—a review article - Martin Klein; Lenka Lapides; Denisa Fecmanová; Ivan Varga (Clinical and Experimental Obstetrics & Gynecology)
Background: Idiopathic or unexplained infertility is a broad subcategory of infertility defined by the absence of obvious or explainable cause, but accounts for at least 25% of all causes. Many possible hidden factors have been discussed over the years, but one of the most prominent and controversial players in this area recently, have been telocytes—newly discovered interstitial cells. Telocytes were first described only 15 years ago, but as of today, they have been observed in almost all organs of the human body including the uterine tubes, uterus and other organs of the female reproductive system. Aside from their vast array of physiological functions such as immune regulation, cell-to-cell signalling, cell-nursing and hormone-sensing, they have been also implicated in the pathogenesis of many different diseases, for which we have coined an original term “telocytopathies”. Methods: We have reviewed relevant articles in English on the topic of idiopathic infertility and telocytes mostly from the last 5 years, using PubMed/MEDLINE, Scopus and Web of Science databases. Results: Quantitative loss and functional derangement of telocytes many not cause any obvious pathological changes, but a subtle, yet important loss of crucial functions of telocytes can lead to unexplained infertility. Discussion: In the uterine tubes, possible mechanisms include changes in the structural and functional integrity of the cellular microenvironment. In the uterus, one of the main proposed mechanisms is immune dysregulation of macrophages and other immune cell populations. In the developing placenta, the main focus is placed on the role of telocytes in immune regulation and decidualisation. All these presupposed pathogenetic factors are still highly speculative, but possibly future research will elucidate the role of telocytes in these processes, which may lead to change of the status of idiopathic infertility, but also of many other “idiopathic” diseases regardless of the organ in question.